Akibat Hukum Terhadap Pihak Ketiga Atas Akta Perjanjian Perkawinan Dibawah Tangan Yang Disahkan Oleh Notaris Setelah Perceraian (Studi Putusan Pengadilan Tinggi DKI. Jakarta Nomor 477/PDT/2019/PT.DKI.) - Hauna Nur Azizah (Indonesian Notary, 2020)
Which  decided that  the  legalization  of  the  marriage  agreement does not apply toward a third party and must be ruled out, therefore the autor is interested in discuss the  legal  consequences  of  the  third  party  involved  and  the  validity  of  the marital assetthat is obtained during the marriage. To solve these problems, a normative juridical  method  with  a  typology  of  descriptive  analytical  was  used.  The  data  analysis was carried out using a statute approach and a case approach. The result of this research show  that  an  under-hand  marriage  agreement  made  by  legitimate  parties  and  binds  the parties with the condition of Section 29 subsection (1) of the Company Law, which allows it to be made under hand and provisions to be held after marriage can be justified based on  the  Constitutional  Court  Decision  Number  69  /  PUU-XII  /  2015  dated  27  October 2016,  where  the  marriage  agreement  is  not  interpreted  as  an  agreement  made  before marriage (prenuptial  agreement)but  can  also  be  made  after  the  marriage  takes  place (postnuptial agreement).The judge in considering the decision and decides to make the Deed  above  which  is  made  before  a  Notary  to  become “..  doesn’t  have  the  value  of evidentiary  and  must  be  ruled  out”. The  marriage  agreement  under-hand  is  considered not validated by a  marriage registrar or a notary that is only  valid  internally (Husband-Wife) toward  a third  party  may  consider that  as  long  as  it  has  not  been  registered  by  a third  party  may  consider  that  the  marriage  is  took  place  with  togetherness  of  marital assets. Keyword  : Marriage  agreement under-hand, legalization of Notary, and Third Party